A case report of coronary artery spasm and takotsubo syndrome: exploring the hidden side of the moon. Issue 1 (11th December 2020) - Lombardi, Marco; Vergallo, Rocco; Liuzzo, Giovanna; Crea, Filippo
Abstract: Background : Takotsubo syndrome (TTS) is a disease characterized by an acute and reversible myocardial injury typically precipitated by stressful and/or emotional triggers. Despite extensive research, its pathogenesis remains incompletely understood. Spasm of epicardial coronary arteries has been proposed as a potential pathogenic factor in TTS. Case summary : Herein, we report the case of a 68-year-old female admitted to the emergency department after developing chest pain in concomitance with an intense emotional stress. A diagnosis of non-ST-segment elevation myocardial infarction (NSTEMI) was made. Coronary angiography disclosed normal coronary arteries, and left ventriculography showed an inferior focal akinesia with basal and apical hyperkinesis, so that a diagnosis of 'focal TTS' was made. Two months later, the patient was re-admitted with NSTEMI, and repeat coronary angiography showed an irregular subocclusive stenosis of a well-developed first obtuse marginal branch. After intracoronary nitroglycerine infusion, a complete recover of the vessel patency was noted, and a diagnosis of epicardial spasm was made. Intracoronary optical coherence tomography was performed to assess a residual 'hazy' region, which confirmed a normal vessel morphology and a residual focal area of spasm without signs of instability. Discussion : Whether TTS and coronary artery spasm are two expressions of the same disease, or rather two separate entities with overlapping mechanisms remains unknown, and further research is warranted to solve this issue. Meanwhile, the opportunity of performing provocative tests for coronary spasm in patients with suspected TTS might be considered to gain more insights into this hypothesis.